CHALLENGES IN EMERGENCY RESPONSE INFRASTRUCTURE: A SYSTEMATIC LITERATURE REVIEW - Abudu, Haruna Domanamwin; Mewomo, Cecilia Modupe; Adjei, Kofi Owusu; Bondinuba, Francis Kwesi (Journal of Civil Engineering, Science and Technology, 2025)
This study identifies critical disaster preparedness and response capacity improvement areas. This study examines the challenges that emergency response infrastructure faces on the global level. The analysis of current trends, case studies, and expert opinions regarding emergency response infrastructure was conducted through a thorough literature review. The study reveals 15 significant challenges and is grouped into 7 categories: resource constraints and infrastructure issues; technological and information disparities; coordination and governance; social, cultural, and religious considerations; urbanisation and population dynamics; vulnerability and risk factors; and community engagement and participation. Moreover, disparities in resource access intensify vulnerabilities in marginalised communities, hindering equitable disaster response outcomes. Insights from this study can inform policymakers, emergency responders, and humanitarian organisations in prioritising investments, developing robust infrastructures, and fostering cross-border collaborations to mitigate disaster impacts effectively. Addressing the identified challenges can improve societal resilience, ensuring more equitable and efficient emergency response efforts that safeguard vulnerable populations and promote community well-being. This study contributes by synthesising diverse perspectives on global emergency response infrastructure challenges, offering a nuanced understanding of the interconnected issues.